Single-cell PCR analysis of the immunoglobulin heavy-chain CDR3 region for the diagnosis of leptomeningeal involvement of B-cell malignancies using standard cerebrospinal fluid cytospins - Hug, Andreas; Storch-Hagenlocher, Brigitte; Haas, Jürgen; Vogt-Schaden, Maria-Elisabeth; Goldschmidt, Hartmut; Wildemann, Brigitte (Journal of the neurological sciences, 2004)
The diagnosis of leptomeningeal B-cell malignancies is based on the identification of malignant B cells in the cerebrospinal fluid (CSF). We have established a polymerase chain reaction (PCR) approach to characterize the clonally diverse gene encoding the immunoglobulin heavy-chain (IgH) third complementarity determining region (CDR3) of single B cells. We demonstrate that single-cell PCR is readily applicable to individual cells derived from routine CSF cytospins and is a powerful method to discriminate monoclonal neoplastic from polyclonal reactive B-cell responses. Single-cell PCR analysis, as a new tool for the diagnosis and monitoring of neoplastic meningitis associated with B-cell malignancies, is particularly important if cytology, immunocytochemistry, flow cytometry and automated gene scanning of CSF samples are unable to detect malignant monoclonal proliferation.